OPPOSITION PARTY AND ELECTORAL POLITICS IN MANIPUR: A HISTORICAL PERSPECTIVE - Singh, OinaDm Muhindro (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The opposition party is a vital component of democratic governance, acting as a check on the authority of the ruling party and assuring representation for a variety of opinions in the political scene. It operates outside of the ruling government and provide alternative viewpoints and policies. Their major responsibility is to scrutinise the acts and policies of the ruling party or coalition, offering criticism and alternative ideas. It is essential in democratic system because it provides checks and balances, ensures responsibility, and represents a wide range of social interests. In a parliamentary system, opposition parties keep the government accountable through debates, questioning in parliament, and offering alternative legislation. It also helps in shaping public opinion through media coverage and grassroots activism. It contests in elections with the goal of attaining power and forming its own government. In light of this framework, the article investigates the role and involvement of opposition parties in the five state assembly elections of Manipur held during the post-statehood period.